FEATURES OF INFORMATION SECURITY FOR MANAGEMENT OF LOGISTICS PROCESSES - GRYSHKO, Viktor; KUSTOV, Vitaliy; TRYASHCHENKO, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article argues that a combination of appropriate software and cutting-edge technology is necessary to handle logistics in any organization. The article also outlines logistics procedures. The logistics process is divided into two subsystems: one related to information and the other related to materials. The article presents a logistics system for converting goods, taking into account the logistics processes of the organization. The article highlights several key characteristics that are common to all logistics processes. These include a close connection with the organization, the absence of an independent sphere of activity, and complete subordination to the primary objectives of the organization. The article emphasizes the importance of focusing on achieving these goals and optimizing costeffectiveness at different points of the logistics sequence. It has been established that the logistics process infrastructure serves as a system of means for the spatial-temporal transformation of the logistic flows of an organization, which operates in organizational and economic conditions. It has been proven that regardless of complexity and direction, the logistics process has the following main classification elements that are essential to mention in its description: planning and forecasting, information support, analysis, control, and managerial decisions. The article evaluates possible directions for enhancing the information support of managing logistics processes in an organization. It also provides an outline of contemporary information technologies. Priority should be given to implementing and developing digital logistics systems for managing transportation flows. Additionally, the use of autonomous vehicles, such as drones and autonomous trucks, for transporting goods should be considered. It is important to include information support for managing logistics processes, which should involve organizing sales activities, digital marketing, e-commerce, and optimizing risk management. These tasks should be carried out using principles, methods, tools, and necessary functions to handle a complex sequence of logistics processes. The approach should be based on a network
Keywords: information support; information flow; logistics; logistics processes; management